Self-control among Al-Qadisiyah University students ( A comparative study ) (Journal of the College of Basic Education, 2022)
The research aims to identify the level of self-control among the students of the University of Al-Qadisiyah (a comparative study) and for the morning studies for the academic year (2020-2021 AD), and to achieve the objectives of the current research, the researchers adopted the scale (Rogers 1986), which was applied to the research community represented by the students of the University of Al-Qadisiyah The sample consisted of (100) male and female students who were randomly selected. The current research aims to identify:1- Detecting the trait of self-control among the students of Al-Qadisiyah University.2- Identifying the statistically significant differences in the research sample in the trait of self-control according to the variable of specializations (scientific - humanities).The researchers used statistical tools to achieve the objectives of the research and reached the results of the research, the most important of which were:The presence of the self-control feature in the research sample. -There is a statistically significant effect of the type of specialization (scientific humanitarian) in the research sample and in favor of the humanitarian specialization.In light of these results, the researchers developed a number of recommendations and suggestions.